Radioimmunoassay of Mammalian Type-C Viral Proteins: Interspecies Antigenic Reactivities of the Major Internal Polypeptide - Parks, Wade P. (1972)
Mammalian type-C viruses contain a major internal polypeptide of about 30,000 daltons that is characterized by both intraspecies and interspecies antigenic reactivities. Radioimmunoprecipitation assays were used for measurement of this protein; the assay was based upon interspecies reactivities of the protein. As little as 5 ng of the group-specific antigen of murine leukemia virus can be measured by radioimmunoprecipitation assays, thus providing an approximate 10,000-fold increase in sensitivity over the standard immunodiffusion procedure. The type-C viruses that were recently isolated from a woolly monkey and gibbon ape each have an interspecies type-C antigenic reactivity. The primate viruses, however, could be distinguished from the type-C viruses of murine, rat, hamster, and feline origin that were more highly related to each other. The interspecies reactivity of the 30,000-dalton polypeptide is an immunological marker of the mammalian type-C viruses, since even with this sensitive assay other mammalian viruses with RNA-dependent DNA polymerase activity did not contain the type-C interspecies antigen.